PENYEBAB KETIDAKHARMONISAN KELUARGA DI SULAWESI SELATAN PERIODE 2007-2021 - Jafar, Rizka; Jannah, Miftahul; Rahman, Abdul (JURNAL SIPAKALEBBI, 2023)
Family disharmony is a condition of a household's inability to maintain the integrity of the family over various problems. One element of national development is maintaining family harmony and welfare. Because the family is an important social manifestation in forming national development forces. This research aims to determine the influence of per capita expenditure, unemployment, education level, and early marriage on family disharmony in South Sulawesi Province during 2007-2021. This type of research is quantitative research with multiple linear regression analysis techniques. It uses secondary data obtained from the Indonesian Central Statistics Agency (BPS) and the Makassar High Religious Court. The results of the research show that 79.44% of the independent variables in the research, namely per capita expenditure, unemployment rate, education level, and the decision to marry young, influence family disharmony in South Sulawesi Province, while the remainder is other variables outside the research influence 20.56%. The research results also show that the variables per capita expenditure, unemployment rate, and early marriage have a significant effect on family disharmony in South Sulawesi during the 2007-2021 period. Meanwhile, the level of education does not affect family disharmony.